Secuelas Psicológicas en Mujeres Víctimas de Violencia de Género (2019)
Psychological sequels, gender violence, women The main objective of this research was to describe the psychological sequelae present in women victims of gender violence. To achieve this, a qualitative research was used, with a phenomenological design where the methodological tool used was the semi-structured interview, which was divided into two main categories: the first, Psychological Sequels, the second, Gender Violence. The population sample consisted of five cases of women victims of gender violence, physical or sexual, with ages between 28 and 40 years of age, who currently have children and are working formally or informally.